Visual structure of Tall-e Bakun painted potteries - Hasan Talaee, Ahmad Salehikakhki,; Naji, Mahan (Opción, 2019)
The current study will review the visual language of the designs on pottery from the Iranian plateau in the third millennium B.C. with a formalist approach. The procedure of analysis was established based on findings in numerous sites located in southwest and south Zagros. Analyzing image elements and design principles revealed a pattern of density of motifs, compositional structure of design and its elements, and type and repetition of motifs. In conclusion, understanding the history of visual arts of a part of Iran and awareness of motifs can pave the way for creating artworks by artists in our country.